Influence of acid-base imbalance and hyperlipidaemia on statin-induced myotoxicity - Taha, Dhiaa A. (2017)
Disturbances in the acid-base balance, such as acidosis and alkalosis, alone or in the presence of postprandial or pathological hyperlipidaemia can alter the pharmacological and toxicological outcomes of statin therapy. Both acid-base imbalance and hyperlipidaemia are quite common among statin users. Statins are commonly prescribed for elderly patients who have multiple co-morbidities such as diabetes mellitus, cardiovascular and renal diseases. These conditions are risk factors for the development of metabolic acidosis. In addition, patients with abnormal plasma lipoproteins levels are usually treated with statins. There is also a general consensus by clinicians to recommend such patients to use unsaturated fat and fatty acids such as olive oil for prevention of cardiovascular and atherosclerotic diseases. The use of such oils is associated with transient but significant elevation in plasma triglyceride-rich lipoproteins (TRL), mainly chylomicrons. The effect of disturbances in acid-base balance on the inter-conversion of simvastatin and pravastatin between lactone and hydroxy acid forms have been investigated in physiological buffers, human plasma, and cell culture medium over pH ranging from 6.8–7.8. The effects of such inter-conversion on cellular uptake and myotoxicity of statins were assessed in vitro using C2C12 skeletal muscle cells under conditions relevant to acidosis, alkalosis, and physiological pH. Results indicate that the conversion of the lactone forms of simvastatin and pravastatin to the corresponding hydroxy acid is strongly pH-dependent. At physiological and alkaline pH, substantial proportions of simvastatin lactone (~87% and 99%, respectively) and pravastatin lactone (~98% and 99%, respectively) were converted to the active hydroxy acid forms following 24 hours of incubation at 37°C. At acidic pH, conversion occurs to a lower extent, resulting in greater proportion of statin remaining in the more lipophilic lactone form. However, pH alteration did not influence the conversion of the hydroxy acid forms of simvastatin and pravastatin to the corresponding lactones. Furthermore, acidosis has been shown to hinder the metabolism of the lactone form of statins by inhibiting hepatic microsomal enzyme activities. Lipophilic simvastatin lactone was found to be more cytotoxic to undifferentiated and differentiated skeletal muscle cells compared to the more hydrophilic simvastatin hydroxy acid, pravastatin lactone, and pravastatin hydroxy acid. Enhanced cytotoxicity of statins was observed under acidic conditions and is attributed to increased cellular uptake of the more lipophilic lactone or unionised hydroxy acid form. Statins association with plasma lipoproteins was examined using an in silico model, artificial chylomicrons-like lipid particles, rat and human lipoprotein fractions under conditions of physiological and altered pH levels. The effect of statins association with plasma lipoproteins on cellular uptake and myotoxicity of these drugs was also assessed at different pH levels using C2C12 cells that overexpress lipoprotein lipase (LPL). Lipophilic simvastatin displayed considerable association with plasma lipoproteins. The association was more significant with the non-polar lipoprotein fractions (TRL and Low-density lipoprotein [LDL]). This association contributed to increased cellular uptake of statins by C2C12 cells through LPL-mediated process, resulting in a higher intracellular concentration of statins in hyperlipidaemic conditions. These high intracellular concentrations of statins induced significantly higher cytotoxicity in hyperlipidaemic environment comparing to normolipidaemic conditions. Furthermore, a combination of low pH environment (representing acidosis) with hyperlipidaemia enhanced the association of lipophilic statins with plasma lipoproteins and increased cellular uptake and myotoxicity of these drugs. These studies suggest that comorbidities such as hyperlipidaemia, especially when coincident with acidosis, can enhance the statin-associated muscle toxicity, and therefore require extra caution and close monitoring by prescribing clinicians. Hydrophilic rather than lipophilic statins could be a preferable choice in this patient population.